ASSESSING REVIEW CONSISTENCY, PRODUCT INFORMATION QUALITY, AND ONLINE IMPULSIVE BUYING TENDENCY: THE MEDIATING PATHWAY OF CUSTOMER ENGAGEMENT - Toding, Luciana Alriani; Wirawan, Kevin; Gaitedy, Novyanti; Syarif, Siti Fadilah; Willar, Ayumi Elizabeth Pricillia; Ardyan, Elia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study examines the influence of review consistency and product information quality on customer engagement and impulsive buying tendencies. The participants in this study consisted of 57 individuals who spontaneously bought on a live-streaming platform. The analytical technique employed in this study is Structural Equation Modeling - Partial Least Squares (SEM-PLS), and the data processing is conducted using WarpPls version 8. The findings of this study suggest that maintaining consistency in reviews and ensuring high-quality of product information might enhance consumer involvement. Additional findings indicate that client contact has the potential to enhance consumers' inclination towards impulsive buying. An important management conclusion of this study is that organizations must guarantee the accuracy, comprehensiveness, and clarity of the product information they supply. This will help to enhance customer engagement and promote impulsive purchase behavior.